A decision-making model to design a sustainable container depot logistic network: the case of the port of Valencia - Palacio, Antonio; Adenso-Díaz, Belarmino; Lozano, Sebastián (Transport, 2018)
In this paper, the design of a maritime container depot logistic network in a hinterland is studied. Containers are a basic tool in multimodal product transportation and all related operations have an impact on the environment due to different externalities such as noise, atmospheric and visual pollution. A three objective optimization model is used to minimize the total network cost, the environmental impact generated by the road transport operations associated with the depots (TI) and the environmental impact generated by the setting up and maintenance of the depots (FI). To determine the environmental impacts of each depot, Fuzzy Analytic Hierarchy Process (F-AHP) is used in both cases. In addition, a fuzzy multiobjective optimization approach has been used to solve the problem. The application case study is based on the Port of Valencia (Spain).First published online 04 November 2015